Relasi Aku dan Liyan dalam Budaya Lejong Masyarakat Manggarai : Kajian Filosofis Berdasarkan Konsep ‘Framework Aku’ menurut Armada Riyanto - Hubertus Herianto (Parahyangan Catholic University, 2021)
Focus of this paper is to find the face of the relationship between ‘I dan Others (Liyan)’ in Lejong culture of Manggaraian society. The methodology which we use is a critical reading of the rites contained in Lejong culture using the concept ‘framework I’ by Armada Riyanto, Indonesian philosopher. This study found that, ‘framework I’ make possible the relationality between I and Others (Liyan). The relationship between I and Onthers (Liyan) in Lejong formed by equality principle. The equality of I and Others (Liyan) in Lejong shown by placing the others as ite and toe ata bana. It means that the other is he who is respected, recognized and valued as being as dignified as ‘I’. The recognition of this equal dignity shown by the rites used to welcome guests, namely reis, raes and raos. The existing rites present various faces of equal relations that exist be- tween I and Others (Liyan) in Lejong, namely intersubjective relations, mutually enrich- ing relations, relations based on openness and relationships that promote love.